An efficient method for simulating light curves of cosmological microlensing and caustic crossing events. Issue 2 (2nd June 2022) - Meena, Ashish Kumar; Arad, Ofir; Zitrin, Adi
ABSTRACT: A new window to observing individual stars and other small sources at cosmological distances was opened recently, with the detection of several caustic-crossing events in galaxy cluster fields. Many more such events are expected soon from dedicated campaigns with the Hubble Space Telescope and the James Webb Space Telescope . These events can not only teach us about the lensed sources themselves, such as individual high-redshift stars, star clusters, or accretion discs, but through their light curves they also hold information about the point-mass function of the lens, and thus, potentially, the composition of dark matter. We present here a simple method for simulating light curves of such events, i.e. the change in apparent magnitude of the source as it sweeps over the net of caustics generated by microlenses embedded around the critical region of the lens. The method is recursive and so any reasonably sized small source can be accommodated, down to sub-solar scales, in principle. We compare the method, which we dub Adaptive Boundary Method, with other common methods such as simple inverse ray shooting, and demonstrate that it is significantly more efficient and accurate in the small-source and high-magnification regime of interest. A python version of the code is made publicly available in an open-source fashion for simulating future events.